2013
DOI: 10.4015/s101623721350035x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on a Developed Wearable Assistive Device (Wad) in Reduction Lumbar Muscles Activity

Abstract: A new wearable assistive device (WAD) was developed to decrease required force on the lumbar spine in static holding tasks. In order to obtain moments on lumbar spine in two conditions, with and without WAD, a biomechanical static model was used for estimation of external moments on lumbar spine. The results of biomechanical models indicated that there was a reduction in the lumbar moment ranging from 20% to 43% using WAD depending on the load and flexion angle. A total of 15 male healthy subjects were tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Pillai et al [ 27 ] reported a 12–48% reduction in RF muscle activity in a drilling task with use of a lower-limb exoskeleton. Other upper-limb exoskeleton studies also showed a 49–62% [ 23 ], 36–56% [ 20 ], 17–23% [ 4 ], and 20–44% [ 21 ] reduction in upper body muscle activities with use of the upper-limb exoskeleton.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Pillai et al [ 27 ] reported a 12–48% reduction in RF muscle activity in a drilling task with use of a lower-limb exoskeleton. Other upper-limb exoskeleton studies also showed a 49–62% [ 23 ], 36–56% [ 20 ], 17–23% [ 4 ], and 20–44% [ 21 ] reduction in upper body muscle activities with use of the upper-limb exoskeleton.…”
Section: Discussionmentioning
confidence: 96%
“…The risk of musculoskeletal disorders in the agricultural sector is higher than in other sectors [ 4 , 5 ]. Awkward working postures occur for more than 50% of daily working hours during agricultural work [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar use of integrated gas springs is found on the Laevo (Laevo, 2017) and BackX (SuitX, 2017). Elastic bands are used on a number of devices, including the Personal Lift Augmentation Device (PLAD) (Abdoli-E, Agnew, & Stevenson, 2006), Smart Suit Lite (SSL) (Imamura, Tanaka, Suzuki, Takizawa, & Yamanaka, 2011), Wearable Assistive Device (WAD) (Heydari, Hoviattalab, Azghani, Ramezanzadehkoldeh, & Parnianpour, 2013), and biomechanically assistive (B.A.) garment (Lamers, Yang, & Zelik, 2017).…”
Section: Passivementioning
confidence: 99%